2015
DOI: 10.1111/jcpt.12305
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a computerized physician order entry system on medical errors with antineoplastic drugs 5 years after its implementation

Abstract: The CPOE system almost completely eliminated MEs with antineoplastic drugs in the Haematology Department. No new types of MEs were observed once physicians had become accustomed to using the system. However, some MEs were not eliminated. Constant diligence is needed to analyse and evaluate MEs associated with the CPOE system and their causes, such that the limitations of CPOE can be identified and overcome and the medication-use process associated with antineoplastic agents improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The different types of CPOE used in the studies are listed in Table 2 . One of the studies reported complete elimination of all CMEs with adequate training and acclimatisation of personnel over a period of 5 years [ 33 ]. Two studies did not provide inferential statistics; however, the number of events pre- and post-CPOE differed significantly (Table 2 , P <0.05) [ 28 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The different types of CPOE used in the studies are listed in Table 2 . One of the studies reported complete elimination of all CMEs with adequate training and acclimatisation of personnel over a period of 5 years [ 33 ]. Two studies did not provide inferential statistics; however, the number of events pre- and post-CPOE differed significantly (Table 2 , P <0.05) [ 28 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 11 studies were published between 2006 and 2018 and had a single-arm design in which the CPOE pre-and post-implementation phases were compared [26][27][28][29][30][31][32][33][34][35][36]. Among these, five studies were from the USA, three from Europe, and three from Asian countries.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Sanchez Cuervo et al indicated that although CPOE could reduce MEs, it may lead to new types of errors, especially in its first implementation. Moreover, they indicated that no new types of MEs were observed once physicians had become accustomed to using the system ( 20 ). In addition, Wu et al stated that several factors had an important role on the efficacy of CPOE such as urgent situations, thus, urgency played a more important role in CPOE numeric typing error-making than typing skills and habits.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, anticancer drugs present a narrow therapeutic index with potentially lethal adverse events. Many studies have highlighted the benefit of computerised prescription (CP) in oncology 1 2. However, CP may lead to the emergence of new errors defined as e-iatrogenesis that can result in unintended consequences 3.…”
mentioning
confidence: 99%